Intra-abdominal desmoid tumor mimicking gastric cancer recurrence: a case report - Okamura, Akihiko (BioMed Central, 2014)
Intra-abdominal desmoid tumors are rare and most often occur in patients with a history of familial adenomatous polyposis, surgery, or pregnancy. We report a case of an intra-abdominal desmoid tumor mimicking the recurrence of gastric cancer. A 57-year-old male had undergone distal gastrectomy for advanced gastric cancer. Serum levels of carcinoembryonic antigen were found to be elevated 27 months after surgery. Computed tomography revealed a 15-mm mass in the mesentery of the transverse colon. In addition, radiotracer fluorodeoxyglucose uptake of the tumor was detected by positron emission tomography. The patient was diagnosed with gastric cancer recurrence, and chemotherapy consisting of cisplatin and S-1 was commenced. After five courses of chemotherapy, although no significant clinical response was seen, no new lesions were seen either. Thus, a curative resection of the recurrent tumor seemed possible, which was successfully performed. Histological examination of the resected specimen revealed spindle-shaped tumor cells with collagen fiber progression; no cancer cells were detected. The tumor was diagnosed as an intra-abdominal desmoid tumor. We report a rare case of an intra-abdominal desmoid tumor that mimicked a recurrent tumor arising from gastric cancer. In patients with history of surgery for intra-abdominal malignancies, it may be difficult to distinguish the recurrence of malignancy from desmoid tumors but the possibility of desmoid tumors must be considered in the differential diagnosis.